Transparency as a principle of activity of public authority bodies - Martynenko, D. (Global Prosperity, 2022)
The article specifies the content and significance of the principle of transparency in the activities of public authorities. The legal regime of transparency provides not only the openness and availability of socially significant information (the so-called passive side of transparency), but also the participation of civil society institutions and business entities in the control over the activities of public administration bodies (the active side of transparency). Implementation of the principle of transparency involves ensuring the right of access to information. Such access to information presupposes the active actions of the subjects of public administration to disclose information about their activities. On the basis of the conducted analysis, the following elements of the legal regime of transparency in the field of public administration are distinguished: openness of information about the system of public administration, free experience in public service and service in local self-government bodies on a competitive basis; openness of information about the activities of public governance bodies, including the publication of regulatory and legal acts, public reporting of bodies, opening meetings, coverage of the administrative decision-making process, publication of the results of the activities of public governance bodies, transparency and availability of information on public spending; participation of citizens, institutions of civil society and business entities in public administration, control over the activities of government bodies; the use of information technologies to cover the activities of public administration bodies; digitization of administrative procedures; judicial protection of the rights of citizens and organizations in the implementation of public governance, the possibility of an administrative appeal in case of violation of the information rights of citizens.